Analysis of players and scenarios of the Iranian aluminum industry with a combination of fuzzy DEMATEL and game theory - Maryam Musavi-Nogholi; Mohammad Taghi Rezvan (تصمیم گیری و تحقیق در عملیات)
Purpose: Futurology of the aluminum industry, as a strategic industry and one of the sustainable development pillars, is contemplated by the government strategists in order to know future against unpredictable elements. The purpose is to identify and analyze the upcoming scenarios of the aluminum industry and, finally, its market analysis, to draw a correct vision of the future and choose the appropriate strategy in this industry.Methodology: Firstly, the key variables affecting the development of the aluminum industry are identified through interviews with experts and specialists in the industry, and the probability of variables is determined by completing a questionnaire; and then based on the extracted variables, specific scenarios are developed. The interactions of the variables will be determined using the fuzzy DEMATEL method and the matrix obtained from this method will be part of the supermatrix of the analysis network process. Game theory will be used in two forms, considering competition and or cooperation among players to analyze the aluminum industry market, such that one can find balancing points among existing situations of players’ strategic options and scenarios of this industry.Findings: The results indicate that the possibility of "increasing inflation" is the most likely and "increasing investment in the country" is the least likely variable, and "lifting sanctions" is the most influential variable and "production and export" is the most impressive variable. Five scenarios as "Iran's difficult scenario in the ordinary world", "Iran's catastrophic scenario in the ordinary world space", "disaster scenario for Iran in the difficult global space", "Iran's developing scenario in the ordinary world space", and "Iran's favorable space scenario in the difficult world space "were ranked. Three main players, namely policymakers, smalters and downstream, were identified and 13 strategic options in the form of investment, pricing, exports, and energy rates in different directions and shapes were extracted. Players’ preferences in different scenarios are explained in the form of 12 modes and, selected modes are extracted for each scenario based on different equilibrium points.Originality/Value: Futurology has been the main subject of this paper, which, by analyzing the aluminum industry and the activities of the main players active in this industry, paints a picture of the future of this industry, including the entire value chain in a five-year horizon.